Development of Test Instruments to Test Students' Understanding of Macroscopic, Sub-Microscopic and Symbolic Levels in Acid-Base Titration Material Using the Rasch Model - Febi Edinda Putri; Faizah Qurrata Aini (Journal of Educational Sciences, 2023)
This study created a test instrument that can test students' understanding of the macroscopic, sub-microscopic and symbolic levels in acid-base titration material that has been tested for validity, reliability, difficulty index and differential power of the questions . This development research uses the Rasch model. The subjects of this study were four lecturers, two high school chemistry teachers and 35 students of SMA N 2 Padang. The object is the quality of the test instrument that meets the criteria of validity, reliability, difficulty index and discriminatory power . Data analysis used the MiniFac and Ministep programs. This study has 10 stages, namely: (1) Defining the construct, (2) Identifying the construct, (3) Designing the items, (4) Testing the product, (5) Analyzing the data, (6) Reviewing the results of the analysis, (7) Reviewing the map wright, (8) Repeat steps 4-7, (9) Claim product quality, (10) Develop documentation. The results showed that the suitability of validation by experts using the MiniFac program was the exact agreement and expected agreement values were very close, namely 95.8% and 95.4%, this indicated that the results of this analysis fit the model and its estimation. Likewise testing of students using the Ministep program. Each item can be said to be valid because it meets the criteria of the MNSQ, ZSTD and PtMean Corr. The instrument is also claimed to be reliable because it has a value of 0.92 . The difficulty index and discriminating power of the items also varied from the easiest to the most difficult.